Ragam Khitobah Taâtsiriyah: Sebuah Telaâah Ontologis - Ridwan, Aang (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2011)
Khitobah Activity is one of daâwah form that posited urgent. As functional, the daâwah form take a model transmission and diffusion of up to date Islamic doctrine, follow manner of social dynamic and religious tradition of moslem society.Â With that character, khitobah taâtsiriyyah can developÂ several modelÂ and form varieties. At least, there are three forms, are: khitobah al-waqiâiyyah, khitobah walimah and khitobah almunadzomah. Khitobah al-waqiâiyyah is khitobah activity concern with the big days momentum of Islam history and national event. Khitobah walimah, concern with tasyakur bin niâmah. Khitobah almunadzomah as done by DKM (The Mosque Posperity Broad), Majlis Taâlim, Islamic Traditional School, Islamic Society Organization, and so on.